2010
DOI: 10.1111/j.1744-7909.2010.00958.x
|View full text |Cite
|
Sign up to set email alerts
|

Coronatine Alleviates Water Deficiency Stress on Winter Wheat Seedlings

Abstract: With the aim to determine whether coronatine (COR) alleviates drought stress on wheat, two winter wheat (Triticum aestivum L.) cultivars, ChangWu134 (drought-tolerant) and Shan253 (drought-sensitive) were studied under hydroponic conditions. Seedlings at the three-leaf stage were cultured in a Hoagland solution containing COR at 0.1 microM for 24 h, and then exposed to 20% polyethylene glycol 6000 (PEG-6000). Under simulated drought (SD), COR increased the dry weight of shoots and roots of the two cultivars si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 40 publications
(39 reference statements)
4
10
0
Order By: Relevance
“…Also, severe drought has more intensive effect than moderate drought (Table 3). These results agree with those of Li et al [28] who observed significant increase in membrane lipid peroxidation of different wheat cultivars grown under water deficit. As a similar response, MDA Fig.…”
Section: Membrane Featuressupporting
confidence: 93%
See 1 more Smart Citation
“…Also, severe drought has more intensive effect than moderate drought (Table 3). These results agree with those of Li et al [28] who observed significant increase in membrane lipid peroxidation of different wheat cultivars grown under water deficit. As a similar response, MDA Fig.…”
Section: Membrane Featuressupporting
confidence: 93%
“…GR was also inhibited in all the surveyed genotypes except in moderately-droughted Gimmaza 9 and 11 as well as stressed Sids 13, Sakha 94 and Giza 186. Reduction in CAT and GR activity in water-unsatisfied wheat was previously noted [28]. Suppressed activity of CAT and GR under stress may result from the reverse effect of stress on protein biosynthesis.…”
Section: Antioxidant Enzymesmentioning
confidence: 59%
“…As shown in Table 2, the results show that RWC and Chlorophyll a/b decreased with the water stress in both fertilizer supply and without fertilizer supply conditions, while the parameter, leaf relative conductivity decreased under the fertilizer supply only under well-watered conditions but greatly increased under water-stressed conditions. Similar results were also reported by previous studies (Legros et al, 2009;Song et al, 2010;Sanchez et al, 1983;Correia et al, 1989;Marulanda et al, 2010;Li et al, 2010;Yousfi et al, 2010). When the treatment was observed up to 60 or 90 days, our result showed that RWC and Chlorophyll a/b was significantly lower and leaf relative conductivity was significantly higher in water-stressed treatment than in the well-watered treatment, but it increased with nutrient supply.…”
Section: Treatment Correlation Coefficient Traitssupporting
confidence: 92%
“…Additionally, GR is a vital constituent of the AsA-GSH cycle and takes part in ROS detoxification via maintaining GSH in its reduced state [37]. Consistent with the results of previous studies of COR-induced stress tolerance in plants [38,39], our results indicated that the positive role of COR-mediated tobacco seedlings to relieve oxidative injury involves improvement in antioxidant enzyme activities.…”
Section: Exogenous Cor Improves Ros Scavenging In Plants By Stimulatisupporting
confidence: 90%